PENINGKATAN PROSES DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL QUANTUM LEARNING DI SEKOLAH DASAR - Megawati Megawati; Reni Novita Sari (Jurnal Muara Pendidikan, 2022)
The problem in this research is science learning in class IV SDN 219/II BTN Lintas Asri is less meaningful and does not provide sufficient opportunities for students to do scientific work. So that science learning outcomes are not optimal. This research aims to describe the application of the quantum learning model in improving science learning processes and outcomes. This type of research is CAR to carry out a series of actions to improve the science learning process in the classroom. This research was conducted in two action cycles. The data collection instrument uses observation sheets and learning achievement tests. Then the data were analyzed qualitatively and quantitatively. The results showed that the teacher's observation sheet in the first cycle reached 63.15% and increased in the second cycle by reaching 81.57%. Student observation sheets in cycle I only reached 48.27%, while in cycle II it managed to increase to 79.31%. Students learning outcomes in the first cycle reached 41.37% completeness, while it increased to 82.75% in the second cycle. Based on the results of the study, it was concluded that the process and learning outcomes of science in class IV SDN 219/II BTN Lintas Asri can be increased through the application of the quantum learning model.